MAKSIM KUANTITAS DAN MAKSIM KUALITAS SERTA IMPLIKATURNYA PADA TAYANGAN MATA NAJWA EPISODE “IRONI HARI-HARI INI” - Pratiwi, Dyah; Assidik, Gallant Kurnia (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to describe the observance of maxims of quantity and maxims of quality, describe violations of maxims of quantity and maxims of quality, and describe the implicatures found in Mata Najwa's episode of "Ironi Hari-Hari Ini". The research data is in the form of utterances spoken by the resource person and also the presenter, namely, Najwa Shihab. Sources of data obtained by watching the show and making a transcript of the data. The data collection technique used is listening, free involvement, conversation and notes. Analysis of research data was carried out with interactive analysis techniques. While the validity of the data is done by data triangulation. The results showed that the process of compliance and violation of the maxim of quantity and maxim of quality as well as their implicatures in the Mata Najwa episode of "Ironi Hari-Hari Ini" included: (1) obedience to the maxim of quantity was 28.1%; (2) compliance with maxim of quality as much as 7.8%; (3) the violation of the maxim of quantity is 25%; (4) violation of maxim of quality as much as 10.9%; (5) conventional implicature as much as 17.1%; (6) non-conventional implicatures as much as 10.9%. With the background of the different sources, this is one of the reasons for the many compliances and violations of maxims that were found.Keywords: Implicature; Maxim of Quality; Maxim of Quantity; Najwa Eyes.